2017
DOI: 10.1039/c7ra07863c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silver/reduced graphene oxide coated polyester fabric for electromagnetic interference shielding

Abstract: In this study, silver/reduced graphene oxide (Ag/RGO) coated polyester (PET) fabrics with dopamine as adhesive agent were prepared through an efficient chemical reduction method under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In both the solely AgNP and Ag-rGO samples, there was a detectable leaching of silver into the saline solution over the 180 min, even though leachant concentrations are seemingly below the values commonly observed for municipal wastewater treatment plants, and well below levels thought to induce cytotoxic effects (e.g., the US Environmental Protection Agency (EPA) sets secondary drinking water limits of 1 × 10 −6 g.L −1 silver) [104][105][106]. Results indicated that small traces of silver leached into the solution up to 1.7 × 10 −7 g•L −1 silver per sample for Ag-rGO and 2.3 × 10 −7 g•L −1 for AgNP, respectively [107,108]. This is in contrast to past reports of leaching between 1.5-5.7 × 10 −3 g•L −1 of silver from various textile samples, by Ureyen et al, under similar testing conditions.…”
Section: Nanoparticle-impregnated Polyviscose Substrate Synthesismentioning
confidence: 99%
“…In both the solely AgNP and Ag-rGO samples, there was a detectable leaching of silver into the saline solution over the 180 min, even though leachant concentrations are seemingly below the values commonly observed for municipal wastewater treatment plants, and well below levels thought to induce cytotoxic effects (e.g., the US Environmental Protection Agency (EPA) sets secondary drinking water limits of 1 × 10 −6 g.L −1 silver) [104][105][106]. Results indicated that small traces of silver leached into the solution up to 1.7 × 10 −7 g•L −1 silver per sample for Ag-rGO and 2.3 × 10 −7 g•L −1 for AgNP, respectively [107,108]. This is in contrast to past reports of leaching between 1.5-5.7 × 10 −3 g•L −1 of silver from various textile samples, by Ureyen et al, under similar testing conditions.…”
Section: Nanoparticle-impregnated Polyviscose Substrate Synthesismentioning
confidence: 99%
“…Zhao et al 11 reported an ingenious and efficient strategy to deposit polyaniline/cobalt−nickel coatings onto lyocell fabrics. Wang et al 12 prepared silver/reduced graphene oxide-coated polyester (PET) fabrics, and Esmaeili et al 13 manufactured superhydrophobic coatings by the solidification of soaking glass and paper substrates in molten AKD. Further, Duan et al 14 compared shielding effectiveness between the electromagnetic shielding fabrics prepared by full penetration method and coating method, respectively, and the results show that the full penetration method has better EMSE value than coating method.…”
Section: Introductionmentioning
confidence: 99%
“…ELD of silver (Ag) on synthetic textiles has been widely reported because it offers high electronic conductivity and can be used for antibacterial and electromagnetic shielding applications. [10][11][12][13][14] However, cotton, a natural textile that is one of the most widely produced textiles for clothing, cannot be readily coated with Ag using ELD because of its extreme surface roughness/ disorder and varying surface energy. Uniformly coating cotton with silver necessitates the use of multistep surface pretreatments, such as chemical etching, coating with adhesive polymers or impregnation with nucleation directors, to encourage metal nano-or microparticle binding on the cotton surface.…”
Section: Introductionmentioning
confidence: 99%